Pemberdayaan Petani Melalui Pelatihan Penggunaan Perangkat Uji Tanah Sawah Pada Sekolah Lapang Kabupaten Pasaman Barat Provinsi Sumatera Barat - Emni Salvia Putri; Lilian Safitri (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
To increase food production, the Ministry of Agriculture through various programs carries out activities that can support farming so as to increase food security. West Sumatra Province is one of continues to increase crop production, especially rice, one of which is Pasaman Regency. In this effort, the Ministry of Agriculture provides equipment in the form of soil testing equipment to field officers to be applied in the field. This activity aims to provide knowledge about the use of Rice Field Soil Test Equipment  for farmers in Tanjung Durian Village, Gunung Tuleh District, West Pasaman Regency. This activity is carried out in the form of providing material and practice in the field. In addition, there was also a question and answer session related to problems found by farmers in the field. From the results of the activity, it can be concluded that the farmers were very enthusiastic during the activity, both in receiving material and in direct practice.